Calling the wind : a story of healing and hope - Ludwig, Trudy; Otoshi, Kathryn (New York : Alfred A. Knopf, 2022)
A Japanese family mourns the loss of a wife and mother by making origami cranes and using the Wind Telephone to communicate their feelings of loss and yearning.
Keywords: Bereavement -- Juvenile fiction; Grief -- Juvenile fiction